Evaluation of seaweed extract and two resistant peach varieties for control of peach leaf curl disease (Taphrina deformans) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Horticultural Science at Massey University - Blakeley, Joanne Elizabeth (Massey University, 1989)
The effectiveness of seaweed extracts for the control of peach leaf curl (Taphrina deformans) on Red Diamond nectarines was compared with a copper fungicide and with two varieties of peach claimed resistant to peach leaf curl. Field and laboratory tests were undertaken. The peach varieties Winiata Gold and Gordon's Glory were tolerant to peach leaf curl under conditions of severe disease pressure. They were more effective than seaweed extracts in the control of the fungus. The seaweed extract, Seagro, did not control peach leaf curl disease on Red Diamond nectarines planted in a randomised complete block design in Palmerston North in 1987. No evidence of fungicidal properties was found in the second year of the study when there were eleven infection periods suitable for the leaf curl fungus. In this season both seaweed extract and copper oxychloride fungicide were ineffective. In laboratory experiments, the seaweed extracts Response, Ecklonia and Carpophyllum had no effect on T. deformans growth. In vitro, T. deformans grew well on a media of potato dextrose agar and 1% peptone. Satisfactory growth was also obtained on whole potato extract but the ease of preparation of the commercial agar mix made it the best option for this study. T. deformans grew more slowly on malt agar and peptone and did not grow at all on Czapek media. Acidifying the PDA media to a pH of 3.5 did not significantly affect T. deformans growth. Quick laboratory tests for comparison of fungal growth on different fungicide/seaweed extract amended PDA plates were compared. The measurement of light absorbance of cell suspensions with a spectrophotometer was quicker than counting cells using a haemacytometer. The petri dish zonal inhibition technique was useful for quantifying the effectiveness of some fungicides against T. deformans. Streptomycin, Benlate, and Rovral had little or no effect on the growth of Taphrina deformans in vitro but Saprol inhibited growth.
Keywords: Peach leaf-curl; Marine algae; Fungicides